Cough • 6: Which investigations are most useful in the diagnosis of chronic cough? - McGarvey, L (BMJ Group, 2004)
There is no consensus as to the best diagnostic strategy for chronic cough. Many protocols combine empirical trials of treatment with laboratory investigations. More precise diagnostic tools and improved therapeutic options are required. Until then, the management of chronic cough will remain a clinical challenge.